PENEGAKAN HUKUM DAN PEMBERDAYAAN MINUMAN TRADISIONAL BERALKOHOL DI NUSA TENGGARA TIMUR: SUATU ANALISIS KEARIFAN LOKAL DAN KEPASTIAN HUKUM - Soraya Yuslani Eoh; Sinthya Daniel (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
The regulation of traditional alcoholic beverages in East Nusa Tenggara, particularly moke and sopi, reflects a complex legal tension between cultural recognition, public health protection, law enforcement, and local economic sustainability. This article examines legal uncertainty and normative conflicts arising from the application of national alcohol control regulations, sectoral licensing rules, food safety standards, consumer protection norms, regional authority, and customary practices. The study uses normative legal research with statutory, conceptual, and prescriptive approaches. The analysis applies the theories of legal certainty, legal pluralism, and responsive regulation to assess whether the existing legal framework can provide proportional protection for traditional producers while preventing public health risks. The findings show that the current regulatory framework tends to classify traditional beverages under a general alcohol control regime without clearly distinguishing ritual use, household production, micro-commercial production, and high-risk commercial distribution. This creates legal vulnerability for small traditional producers and weakens predictable law enforcement. At the same time, cultural recognition cannot justify unregulated circulation, unsafe production, youth consumption, or harmful distribution practices. The article argues for a limited, conditional, and supervised responsive regulatory model based on local wisdom, public health standards, and legal certainty. The proposed model includes legal classification, simplified registration for traditional producers, alcohol-content testing, hygiene standards, labeling, age restrictions, collaborative supervision, proportional sanctions, and community-based economic empowerment.